Dyslipidemia Is Negatively Associated With the Cumulative Live-Birth Rate in Patients Without PCOS Following IVF/ICSI - Liu, Zhenteng; Cong, Jianxiang; Liu, Xuemei; Zhao, Huishan; Lai, Shoucui; He, Shunzhi; Bao, Hongchu (Frontiers in Physiology, 2021)
Objective: To evaluate the effect of dyslipidemia on the cumulative live-birth rate (cLBR) in patients without polycystic ovary syndrome (PCOS) undergoing in vitro fertilization/intracytoplasmic sperm injection–embryo transfer (IVF/ICSI–ET) cycles. Methods: A total of 1132 patients from the Yantai Yuhuangding Hospital Affiliated to Qingdao University from January 2016 to December 2017 were retrospectively included. The subjects were distributed into two groups based on their lipid profiles, namely dyslipidemia group (n= 195) and control group (n=937). The clinical and laboratory parameters of the two groups were analyzed and a multivariate logistic regression analysis of the cLBR was conducted. In addition, subgroup analysis was carried out to avoid deviation according to body mass index (BMI). Results: Patients with dyslipidemia had significantly greater BMI and longer duration of infertility, as well as lower antral follicle count and basal follicle-stimulating hormone level compared with patients without dyslipidemia. Stratified analysis showed that dyslipidemia was associated with a significantly higher total gonadotrophin dosage required for ovarian stimulation as well as lower number of oocytes retrieved, independent of obesity. The live-birth rate in fresh cycle and cLBR were higher in the normal group, although the difference between the groups was not significant (54.9% vs 47.3%, P = 0.116; 67.6% vs 62.1%, P = 0.138). However, multivariate logistic regression analysis adjusting for potential confounders showed that dyslipidemia was negatively associated with cLBR (OR, 0.702, 95% CI, 0.533 – 0.881, P =0.044). Conclusion: Our findings demonstrate for the first time that dyslipidemia has a deleterious impact on cLBR, independent of obesity, in non-PCOS population considered to have good-prognosis. Assessment of serum lipid profiles as well as the provision of nutritional counseling is essential for increasing successful outcomes in assisted reproductive techniques.